(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2011)
The inflation phenomenon inherent to all economies in the world, including Iraq, and to find out the reasons for this phenomenon must be measured impact on the national economy, and is the index of consumer prices of the most common measure of inflation in order to find the means and the treatments needed and this can be reached through the study of the role of aggregates Commodity and its impact on the general trend of cash inflation, in Iraq for the period 2004 2009 to determine the groups lead to inflation in Iraq, where it emerged that the group rent is ranked first in the proportion of its contribution to the index of consumer prices, and food group is ranked second. The fuel and lighting group ranked third.